Prevalence and Risk Factors of Hyperuricemia in the Urban Health Checkup Population in Xinjiang, China: A Cross-Sectional Study - Wu X; Zhou M; Bu J; Chang Y; Mahan Y; Lu H; Zhang Y; Zhang X; Wang Z; Zhou L (Dove Medical Press, 2023)
Xuanxia Wu,1,* Mingming Zhou,2,* Juan Bu,1 Yuwen Chang,2 Yeledan Mahan,1 Huanhuan Lu,2 Yanmin Zhang,3 Xiaoling Zhang,1 Zhaoxia Wang,1 Ling Zhou1 1Medical Research and Transformation Center, People's Hospital of Xinjiang Uygur Autonomous Region, Urumqi, Xinjiang, People's Republic of China; 2Health Management Center, People's Hospital of Xinjiang Uygur Autonomous Region, Urumqi, Xinjiang, People's Republic of China; 3Scientific Research and Education Center, People's Hospital of Xinjiang Uygur Autonomous Region, Urumqi, Xinjiang, People's Republic of China*These authors contributed equally to this workCorrespondence: Ling Zhou, Medical Research and Transformation Center, People's Hospital of Xinjiang Uygur Autonomous Region, No. 91 Tianchi Road, Urumqi, Xinjiang, 830001, People's Republic of China, Tel +86-13609959575, Email zlrmyy@sina.comPurpose: In this study, the aim was to investigate the prevalence and risk factors of hyperuricemia (HUA) in the urban health checkup population in Urumqi, Xinjiang, and thus provide clues for the prevention of HUA.Methods: People who attended medical examinations from May 2021 to June 2022 at a hospital in Urumqi, Xinjiang, were selected for evaluation based on their general information, physical examination results, and laboratory test results. The chi-square test was used to determine whether there was a difference in the prevalence of HUA among participants with different characteristics. Using logistic regression analyses, risk factors for HUA were identified.Results: There were 8722 participants diagnosed with HUA, with an overall prevalence of 26.96%. The prevalence in men was 37.72%, significantly higher than in women (13.29%). Participants were characterized by a multiethnic composition, with Han (28.61%), Hui (27.88%) and Manchu (38.46%) being the three ethnicities with the highest prevalence. According to logistic regression analyses, HUA was associated with age, ethnicity, residence, marital status, body mass index (BMI), diastolic blood pressure (DBP), fasting blood glucose (FPG), triglyceride glucose (TyG) index, abdominal obesity, and dyslipidemia differently in males and females.Conclusion: The prevalence of HUA was high in the urban health checkup population in Urumqi, Xinjiang, particularly among men and youth. The early intervention for HUA should be enhanced to reduce the risk of cardiovascular disease and other related conditions.Keywords: hyperuricemia, ethnicity, prevalence, risk factors, epidemiology